Gestión de negocio y su incidencia en los ingresos económicos de las familias por reciclaje de residuos sólidos de la cooperativa de vivienda villa franca del cantón Quevedo año 2023. - Lozano Mendoza, Susy Jannet (2024)
The present research focused on analyzing the impact of business management on the economic incomes of families engaged in solid waste recycling in the Villa Franca Housing Cooperative of Quevedo canton during the year 2023. Specifically, it aimed to identify the income levels generated by these activities, determine the strengths, opportunities, weaknesses, and threats of recycling businesses, and propose efficiency strategies for business management. The research was based on a mixed approach, combining quantitative and qualitative methods. Surveys were conducted with a representative sample of families to collect data on their incomes and recycling practices. Additionally, an interview was conducted with a recycler from the sector. The results revealed that, while recycling represents a significant source of income for the families, the economic levels are still limited due to deficiencies in business management, lack of access to markets, and resources. Strengths identified include the experience and commitment of the families, but weaknesses such as low training and lack of organization were also noted. External threats such as competition and fluctuations in recycled material prices were detected. Based on the findings, strategies are proposed that include training in business skills, strengthening associativity, and linking with key actors from the public and private sectors.